Peningkatan Kemampuan Pemahaman Konsep Program Linear Siswa Kelas XI Melalui Discovery Learning Berbantuan Powerpoint Interaktif - Lakindima, Febriani Lorita; Madu, Aleksius (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2024)
The low concept understanding ability of students in class XI MIA 4 SMA Negeri 9 Kupang is the reason for researchers to conduct research. This study was conducted to describe the improvement of the ability to understand the concept of linear program in students of class XI MIA 4 SMA Negeri 9 Kupang by applying the discovery learning model assisted by interactive powerpoint media. The method used is Classroom Action Research (CAR) which refers to the Kemmis & Mc Taggart model with 4 steps, namely planning, action, observation and reflection. Data collection was done by observation and test. This research was conducted in class XI MIA 4 SMA Negeri 9 Kupang with 32 students. The results showed that the average result of concept understanding test at the end of cycle I was 67.5, then increased to 77.2 in cycle II. Classical concept understanding of each indicator also increased from cycle I to cycle II. The teacher activity score reached 100 in cycle I and cycle II. In addition, the student activity score also increased, namely 92.5 in cycle I and reached 100 in cycle II. Thus, it is concluded that the use of discovery learning model assisted by interactive powerpoint can improve students' concept understanding on linear program material